Etoposide Triggers Cellular Senescence by Inducing Multiple Centrosomes and Primary Cilia in Adrenocortical Tumor Cells - Yen-Ni Teng (Cells, 2021)
Etoposide (ETO) has been used in treating adrenocortical tumor (ACT) cells. Our previous study showed that ETO inhibits ACT cell growth. In the present study, we show that ETO treatment at IC50 (10 μM) inhibited ACT cell growth by inducing cellular senescence rather than apoptosis. Several markers of cellular senescence, including enlarged nuclei, activated senescence-associated β-galactosidase activity, elevated levels of p53 and p21, and down-regulation of Lamin B1, were observed. We further found that ETO induced multiple centrosomes. The inhibition of multiple centrosomes accomplished by treating cells with either roscovitine or centrinone or through the overexpression of NR5A1/SF-1 alleviated ETO-induced senescence, suggesting that ETO triggered senescence via multiple centrosomes. Primary cilia also played a role in ETO-induced senescence. In the mechanism, DNA-PK-Chk2 signaling was activated by ETO treatment; inhibition of this signaling cascade alleviated multiple ETO-induced centrosomes and primary cilia followed by reducing cellular senescence. In addition to DNA damage signaling, autophagy was also triggered by ETO treatment for centrosomal events and senescence. Importantly, the inactivation of DNA-PK-Chk2 signaling reduced ETO-triggered autophagy; however, the inhibition of autophagy did not affect DNA-PK-Chk2 activation. Thus, ETO activated the DNA-PK-Chk2 cascade to facilitate autophagy. The activated autophagy further induced multiple centrosomes and primary cilia followed by triggering senescence.